Lead removal from synthetic wastewater by biosorbents prepared from seeds of Artocarpus Heterophyllus and Syzygium Cumini. (January 2022) - Giri, Deen Dayal; Alhazmi, Alaa; Mohammad, Akbar; Haque, Shafiul; Srivastava, Neha; Thakur, Vijay Kumar; Gupta, Vijai Kumar; Pal, Dan Bahadur
Abstract: The present investigation deals with removal of lead (Pb +2 ) ions from waste water using biosorbent prepared from seeds of Artocarpus heterophyllus (SB Ah ) and Syzygium cumini (SB Sc ). Biosorbents surface has been characterized through FT-IR spectroscopy to probe the presence of functional groups. Response surface methodology enabled optimized conditions (Pb +2 concentration 2 μg/mL, pH 5.8 and bioadsorbent dose 60 mg) resulted in Pb +2 removal ~ 96 % for SB Ah and ~ 93 % for SB Sc at agitation speed 300 rpm. The adsorption capacity has been found to be 4. 93 mg/g for SB Ah and 3. 95 mg/g for SB Sc after 70 min. At optimal experimental conditions, kinetics of biosorption was explained well by inter-particle diffusion model for SB Ah ( R 2  =  0.99 ) whereas Elovich model best fitted for SB Sc ( R 2  =  0.98 ). Further, both the biosorbents followed Temkin adsorption isotherm model. Graphical abstract: Image 1 Highlights: Lead biosorption using Artocarpus Heterophyllus and Syzygium Cumini biosorbents. The maximum adsorption capacity of Artocarpus Heterophyllus was 4.93 mg/g. Optimum Lead removal was about 96% using Artocarpus Heterophyllus bio-adsorbent. The kinetic studies well explained in terms of Temkin and Elovich model, respectively.